<span>My answer -
f(x)=x^3+2
To find the inverse function f(x)^-1 , we will assume"
y=x^3+2
y-2= x^3
==> x= (y-2)^1/3
==> f(x)-1= (x-2)^1/3</span>
P.S
Happy to help you have an AWESOME!!!!! day
Y = 2x - 5
3x + 8y + 32 = 56
3x + 8(2x - 5) + 32 = 56
3x + 8(2x) - 8(5) + 32 = 56
3x + 16x - 40 + 32 = 56
19x - 8 = 56
<u> + 8 + 8</u>
<u>19x</u> = <u>64</u>
19 19
x = 3.4
y = 2(3.4) - 5
y = 6.8 - 5
y = 1.8
(x, y) = (3.4, 1.8)
Answer:
GHF = EDF
Step-by-step explanation:
Those two tringles are the only even triangles.
1. X=3, 2. X=4, 3. X= 95/2